Nutritional composition and antioxidant activities of ficus carica l. fruits and leaves from Saudi Arabia - Hilal Alqathama, Fatimah Ghazi (2012)
Traditional medicines derived from medicinal plants are used by about 60% of the world’s population. Fruits and herbs contain constituents which have antioxidant properties and may have an inhibitory effect on free radical-induced oxidative damage to biological substances and tissues. Studies of the effective antioxidants in fruits and herbs may provide a great potential in prevention of disease. Ficus carica have been identified as one of the nutritional sources of antioxidants. In this study the total phenolic compounds, antioxidant activity and nutritional value in F. carica fruits and leaves from Saudi Arabia was investigated. The total phenolic content (Folin-Ciocalteu assay), antioxidant capacity FRAP assay (Ferric Reducing Antioxidant Power) and DPPH assay (1, 1-diphenyl-2-pircrylhydrazyl) were determined (methanol and aqueous extract using solvent. In addition, vitamins C and E contents in Ficus carica was also investigated using high performance liquid chromatography (HPLC),as well as mineral using atomic absorption spectrophotometeric (AAS) methods was also evaluated. This research was focused on two species of F. carica. Both Hamat and Balas were differentiated according to the size of fruits and leaves. The results indicated that the Hamat fruit had greater antioxidant capacity, total phenols, and ascorbic acid content than Balas fruits. Aqueous extract of Hamat had a significantly much higher content of total phenolic 347.31±4.38 mg GAE/100g while methanolic extract 229.15 ±1235 mg GAE/100g. The aqueous extract of Hamat had the higher DPPH radical scavenging activity 83.67±1.19% than Balas fruit 46.02±2.87%. Balas leaf aqueous extract achieved the higher percentage of radical scavenging activity 74.58±1.60% compared to methanolic extract 63.29±2.5174%. Balas fruit had the high carbohydrate content 19.2±0.17 and low fat content 0.3±0.14 g /100 g. The Balas leaf had high protein content 5.1 ±0.46 and fat content 1.3 ±0.35 g /100 g. Additionally,both leaves and fruits were shown to contain high amounts of minerals as well as vitamins C and E. In summary, both F. carica fruits and leaves are good sources of dietary antioxidants and processing products as dietary supplements. The F. carica are rich in mineral elements especially in calcium and potassium and also good nutritional composition. F.carica seems to contain high amounts of phenolic compounds with antioxidant activities as well as a good natural source of antioxidants which may potentially reduce the oxidative stress (triggered by chronic diseases). Thus, F. carica could be considered as an alternative and potential source of natural antioxidant. Generally, the present study showed Ficus carica juice and its components are good source of macronutrients. F. carica juices are rich in antioxidant vitamins. In the current study, the DDPH and FRAP indicates a strong antioxidant activities, this could be due to total phenolic content and vitamins of F. carica juice.